Reasons why we read blogs and memorial pages of people who lost a child. Life motives of emotional rubberneckers. Issue 2 (7th February 2021) - Chudzicka-Czupała, Agata; Basek, Agata
Abstract: Researchers have been interested in the subject of accompanying individuals who experienced a child's terminal illness and death, sharing their grief online. Using The Reiss Motivation Profile and qualitative methods, the authors identified the life motives of emotional rubberneckers–grief blog and memorial page readers. Key reasons for the regular behavior of this kind are found: interest in the protagonist's health, compassion, will to help, and sense of bonding. Such activity provides support to the respondents. Readers' important life motives include the substantial need to care for their loved ones, to be needed, emotional stability, and a low need for power.